2022
DOI: 10.2463/mrms.mp.2020-0182
|View full text |Cite
|
Sign up to set email alerts
|

Combining the Tumor Contact Length and Apparent Diffusion Coefficient Better Predicts Extraprostatic Extension of Prostate Cancer with Capsular Abutment: A 3 Tesla MR Imaging Study

Abstract: To assess the diagnostic performance of the tumor contact length (TCL) and apparent diffusion coefficient (ADC) for predicting extraprostatic extension (EPE) of prostate cancer with capsular abutment (CA).Methods: Ninety-three patients with biopsy-proven prostate cancer underwent 3-Tesla MRI, including diffusion-weighted imaging (b value = 0, 2000 s/mm 2 ) and radical prostatectomy. Two experienced radiologists, blinded to the clinicopathological data, retrospectively assessed the presence of CA on T2weighted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…Granja et al predicted EPE using ADC and obtained a sensitivity of 83% with a specificity of 61% at the cutoff value of 0.87×10−3 mm2/s (28). While Ito et al reported a sensitivity of 84.2% and a specificity of 59.0% at the cutoff value of 0.63×10-3 mm2/s (29). The reported sensitivity and specificity in above mentioned studies were similar to our results.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…Granja et al predicted EPE using ADC and obtained a sensitivity of 83% with a specificity of 61% at the cutoff value of 0.87×10−3 mm2/s (28). While Ito et al reported a sensitivity of 84.2% and a specificity of 59.0% at the cutoff value of 0.63×10-3 mm2/s (29). The reported sensitivity and specificity in above mentioned studies were similar to our results.…”
supporting
confidence: 90%
“…Ito et al reported that the combination of LCC and ADC cutoff values yielded an area under the curve (AUC) of 0.82. Their specificity (84.6%) and accuracy (81.0%) of the combined values were superior to their individual values (29). In our current study, the combination of ADC with LCC and tumor size (Model I) yielded an AUC of 0.803.…”
mentioning
confidence: 50%
“…Conversely, benign tumors have relatively low cell density and a large tissue gap, so the free diffusion movement of water molecules is relatively free, manifested by a high apparent diffusion coefficient. The apparent diffusion coefficient has been confirmed to have high value in identifying various malignant tumors (16)(17)(18)(19). Zheng et al found that the apparent diffusion coefficient had a high predictive value for the response to chemotherapy in gastrointestinal cancer patients with liver metastases (20).…”
Section: Discussionmentioning
confidence: 99%